EFFECTS OF TEMPERATURE AND SALINITY ON THE SEEDS GERMINATION OF RETAMA RAETAM (FORSSK.) WEBB. SCARIFIED WITH SULFURIC ACID - Mehdadi, Z.; Bendimered, F. Z.; Dadach, M.; Aisset, A. (University of Eloued جامعة الوادي, 2017)
The present study consists of the elimination of tegumentary inhibition affecting seeds of Retama raetam by the chemical scarification. This pretreatment was carried out using pure sulfuric acid (98 %) and the seeds' germinative behavior was studied in the laboratory under controlled conditions of temperature and salinity. The results reveal that the chemical scarification by the sulfuric acid during six hours, had favored the germination of seeds which were incapable of germinating. The thermal optimum of germination expressed by the highest germination capacities and speeds as well as the shortest average times of germination and latency times corresponded to 20 Â°C and 25 Â°C. At low temperatures (0 Â°C and 5 Â°C) and high temperatures (35 Â°C and 40 Â°C), the germination was not possible.The seeds of R. raetam are sensitive to salinity, when the NaCl concentration increases the rate of germination decreases. The threshold of tolerance was recorded at 272 mM, from which the germination was inhibited.Â Â Â Â Â
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Retama raetam; chemical scarification; germination; temperature; salinity